Vestibular incision subperiosteal tunnel access technique with platelet-rich fibrin compared to subepithelial connective tissue graft for the treatment of multiple gingival recessions: A randomized controlled clinical trial - Bukkapatnam Venkata Subbareddy; Penmetsa S Gautami; C D Dwarakanath; Panda Kausalya Devi; Parimisetti Bhavana; K Radharani (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to compare the effectiveness of root coverage through vestibular incision subperiosteal tunnel access (VISTA) technique using platelet rich fibrin (PRF) or subepithelial connective tissue graft (SCTG) in multiple gingival recessions. Materials and Methods: A total of 20 patients with multiple gingival recessions were included, and 10 subjects were randomly allocated to test group (VISTA with PRF) and 10 patients to control group (VISTA with SCTG). Clinical parameters were recorded at baseline, 3 months, and 6 months. Patient's response toward the treatment was also assessed by questionnaire. Results: All the clinical parameters in the study have showed better results in test group when compared to control group after a follow up period of 6 months with statistical significance. Conclusion: The results of the present study suggested that multiple gingival recessions can be successfully treated with both procedures, but better root coverage and a greater increase in keratinized tissue were achieved with the VISTA technique with SCTG. All the patients in both groups felt it was worth undergoing the treatment.